Continuous Intravenous Inotropic Support for Advanced Heart Failure: Palliative Considerations. (2nd January 2022) - McPherson, Alexandra; Nguyen, Cindy; Groninger, Hunter; Anderson, Kelley M.; Henderson, Paul; Rao, Anirudh
Abstract: The global prevalence of heart failure (HF) is increasing. Advancements in guideline-directed medical and device therapy have resulted in improved survival. Thus, there are more patients living – and living longer – with advanced HF. Only a small proportion of these patients are deemed appropriate for advanced surgical intervention (mechanical circulatory support or heart transplantation), and even if offered, some may decline such interventions if not aligned with their overall goals and values. Therefore, a growing number of patients with advanced HF receive chronic intravenous inotropic support (CIIS) for palliation of symptoms. Despite increased use, clinical evidence supporting use of palliative inotropes remains limited. However, available data suggest improvements in functional class, health-related quality of life (HRQoL) indicators, symptom burden, hemodynamic parameters, and possibly rehospitalization. While initial concerns regarding increased mortality have been assuaged in the modern era of guideline-directed medical therapy, palliative inotropes are certainly not without burden. Risks of infection and medication-related adverse effects, need for routine laboratory monitoring, frequent dressing changes, and presence of a reliable caregiver must be carefully considered prior to initiation. This review addresses pharmacology, guideline recommendations, benefits and burdens, considerations related to hospice and end-of-life care, and future directions of CIIS in advanced HF care.